Public Perception on Historical Landscape of Ethnic Immigrant Heritage in Heritage City of Baubau - Syahadat, Ray March; Arifin, Nurhayati H.S.; Arifin, Hadi Susilo (KOMUNITAS: International Journal of Indonesian Society and Culture, 2014)
As a one of the heritage cities in Indonesia, Baubau has many historical heritages which are not only created by local ethnics but also by immigrants. There are three historical landscapes created by the immigrants like China Town by Chinese, Waliabuku by Bugisnese, and Ngkaring-Ngkaring by Balinese. Until now, proper management to preserve the landscapes does not exist and it remains unknown whether this phenomenon is caused by the public perception who think that historical landscapes of immigrants as an unimportant heritage. The objective of this study is to investigate the public perception of historical landscapes that are created by immigrant in Baubau city as an heritage city in Indonesia. The results of survey show that the public regard all historical landscapes must be preserved. However, the landscapes created by the ethnic of Chinese have the lowest degree of public selection as compared to the ethnics of Bali and Bugis. The situation is triggered by the stereotype on the ethnic of Chinese which state that they tend to be more closed and reserved. Sebagai salah satu kota pusaka di Indonesia, Baubau memiliki banyak peninggalan sejarah bukan hanya yang dibentuk oleh etnis lokal, tetapi juga oleh etnis pendatang. Setidaknya terdapat tiga lanskap sejarah yang dibentuk oleh etnis pendatang yaitu lanskap pecinan oleh etnis Tionghoa, lanskap Waliabuku oleh etnis Bugis, dan lanskap Ngkaring-Ngkaring oleh etnis Bali. Sampai saat ini belum ada pengelolaan untuk melestarikan ketiga lanskap tersebut dan belum diketahui apakah fenomena ini dipengaruhi oleh persepsi masyarakat yang merasa lanskap peninggalan etnis pendatang tidaklah penting? Tujuan penelitian ini yaitu mengkaji persepsi masyarakat terhadap lanskap sejarah peninggalan etnis pendatang sebagai aset pusaka Kota Baubau sebagai kota pusaka Indonesia. Hasil yang diperoleh dari survei yang dilakukan, masyarakat umumnya menganggap seluruh lanskap sejarah harus dilestarikan tidak memandang apakah dibentuk oleh etnis lokal atau pendatang. Meskipun demikian, lanskap yang dibentuk oleh etnis Tionghoa memiliki derajat pemilihan paling rendah dari lanskap yang dibentuk etnis Bali dan Bugis. Hal ini disebabkan oleh adanya stereotip akibat karakter etnis Tionghoa yang dianggap masyarakat cenderung tertutup di Kota Baubau.